METHODOLOGICAL APPROACHES TO ASSESSING THE EFFECTIVENESS OF INTERNATIONAL INTEGRATION ASSOCIATIONS - Kh.N. Mursalova (Academic Journal of Physical and Chemical Sciences, 2019)
In the article, the author attempted to build a unified approach to measuring the effectiveness of integration associations regardless of their regulatory formats and species. existing approaches were analyzed to achieve this goal, while composite index methods were subject to detailed analysis. The author reveals the essence of this method, shows their main four subspecies, identifies their differences, advantages and disadvantages. The limitations of using the composite index technique in terms of compliance with the aggregation of indicators are given. It is proposed to use a three-stage method of constructing a composite index of regional integration taking into account these limitations. An important step in the development of a composite index is the determination of the significance (weight) of each indicator (sub-index), which can be determined using mean, parametric and nonparametric methods. For each of these methods, the specific characteristics peculiar to each of them are given. The results of the study made it possible to develop basic methodological principles for the formation of indicators of the composite index for measuring the effectiveness of integration. Moreover, the author justified possibility of joint use of the methods of aggregation of indicators considered in the work, at the same time it has been revealed that the composite index using the method of the main components is the most informative. Major results and conclusions of a research can be applied in the course of measurement of efficiency and the level of integration associations integratedness for matching and comparing relevant indicators of several integration associations.